Analyzing the temporal relation between virality and success in the Brazilian music market - Oliveira, Gabriel P.; Silva, Ana Paula Couto da; Moro, Mirella M. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2024: Anais do LI Seminário Integrado de Software e HardwareDO - 10.5753/semish.2024.2656, 2024)
Content virality on social media platforms is essential to modern digital culture. In music, viral songs often gain widespread attention through catchy melodies, relatable lyrics, and captivating visuals. Indeed, social platforms have reshaped music consumption, with viral trends often leading to mainstream success. This study investigates the relationship between music virality and success in Brazil by analyzing their evolution in streaming platforms over time. Through correlation and Granger Causality analyses, we explore the dynamics between these facets of music popularity. Our results show that virality can be used to forecast future success and vice versa, but this cannot be generalized to all songs. Such findings reinforce the differences between the concepts of virality and success besides their symbiotic relationship driven by social platforms.